Predictors of successful weaning from veno-arterial extracorporeal membrane oxygenation (V-A ECMO): A systematic review and meta-analysis. - Henry R Hsu; Praba Sekhar; Jahnavi Grover; David H Tian; Ciaran Downey; Ben Maudlin; Chathuri Dissanayake; Mark Dennis (PLoS ONE)
Background Venoarterial extracorporeal membrane oxygenation (V-A ECMO) use to support patients in cardiac failure is increasing. Despite this increased use, predicting successful weaning from ECMO can be challenging, no uniform guidelines on weaning exist. Therefore, we completed a systematic review to evaluate prognostic factors that predict successful weaning from V-A ECMO. Methods Following the PRIMSA guidelines, a systematic literature search of Medline, Embase, SCOPUS and CENTRAL identified original research studies of patients requiring V-A ECMO where weaning was attempted. Data was collected on demographic factors and weaning protocol, biomarkers, haemodynamic, echocardiographic factors for the successfully weaned (SW) and not successfully weaned (NSW) groups. Two investigators reviewed studies for relevance, extracted data, and assessed risk of bias using the ROBINS-I tool. The study was registered on the international prospective register of systematic reviews (PROSPERO ID# CRD42022366153). Results 1219 records were screened, of which 20 studies were deemed sufficient to be included in the statistical analysis based on pre-specified criteria. Factors associated with successful weaning were higher left ventricular ejection fraction (LVEF) (MD 9.0, 95% CI 4.1-13.8; p < 0.001) and left ventricular outflow tract velocity time integral (LVOT VTI) at time of weaning, (MD 1.35, 95% CI 0.28-2.40 lactate at admission (MD -3.2, 95% CI -4.8 to -1.5, p < 0.001), and CK-MB at admission (MD -4.11, 95%CI -6.6 to -1.6, p = 0.001). Critical appraisal demonstrated moderate-high risk of bias owing to confounding and low sample sizes. Conclusion In patients on V-A ECMO support being assessed for weaning multi-parametric assessment is required. Moderate-high heterogeneity and low sample sizes warrant higher-quality studies to help guide decisions to wean patients from V-A ECMO.